Called to stay - Breakey, Caleb Jennings, 1986- (Eugene, Oregon : Harvest House Publishers, 2013)
Will you stay? Caleb Breakey prays to God you do. In Called to Stay Breakey takes a refreshingly honest look at the church, the problem of Millennials leaving, and the stark reality of why the church desperately needs them. He holds nothing back as he unleashes an ambitious rallying cry to heal the church and inject his generation's desire for truth, passion, and conviction into other believers. Caleb knows that answering the challenge of his own generation leads to a transformed church. And a changed church can change the world. - Back cover.
Foreword / Jefferson Bethke -- Part 1 : Why you shouldn't abandon the body. Save the girl -- Why you must stay -- Infiltrating Q & A -- Part 2 : If you want to serve your Savior. Where to start -- Who you must embrace -- What comes next -- How to infiltrate : one -- How to infiltrate : to -- Part 3 : Age of the infiltrator. When to leave -- Staying -- A note from the author -- A conversation with Caleb Breakey -- Tweetables.
Includes bibliographical references.
Keywords: Generation Y -- Religious life; Young adults -- Religious life; Church; Christian life